ANALISIS PENGARUH MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI KANTOR KECAMATAN TANAH SIANG SELATAN KABUPATEN MURUNG RAYA - Noorhayati Noorhayati (Universitas Muhammadiyah Kalimantan Timur, 2019)
The purpose of this study was to analyze: 1) whether the motivation has a significant impact on performance of employees of office Kecamatan Tanah Siang Selatan Kabupaten Murung Raya, and 2) whether the motivation has a positive and significant on performance of employees of office Kecamatan Tanah Siang Selatan Kabupaten Murung Raya. Data about those variable was collected by conduct interviews with questionnaire. The sample is selected by using the technique saturated samples (cencus), which totaled 30. The hyphoteses are tested using singgle regression analysis and bivariate correlation with analysis-pearson correlation by SPSS for Windows 19.0. The result showed that : 1) the motivation has a significant impact on performance of employees of office Kecamatan Tanah Siang Selatan Kabupaten Murung Raya, this is evidenced by the results calculations F statistics 11.526 (sig. 0.000) is greater than F table is 4.20 with alpha 5 % and by the results calculations t statistics 3.395 (sig. 0.002) is greater than t table is 2.048 (sig. 0.05); 2) the motivation has a positive and significant correlation on performance of employees of office Kecamatan Tanah Siang Selatan Kabupaten Murung Raya, this is evidenced by the results calculations r statistics 0.540 (sig. 0.002) is greater than r table is 0.361 (sig. 0.05).